The Influence of The Multimedia-Based Glenn Doman Method Beginning Reading Interest of Grade II Elementary School Students: Pengaruh Metode Glenn Doman Berbasis Multimedia terhadap Minat Membaca Permulaan Siswa Sekolah Dasar Kelas II di SDN Ketegan - Fadlillah, Fani; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2023)
The low interest in reading in students greatly affects the ability to read early. The effect of the multimedia based glenn doman method on the reading interest of elementary school students in grade II at SDN Ketegan. the method developed by glenn doman utilizes multimedia technology, by teaching students to read and recognize letters with flash card. So that students will have the ability to be confident, imaginative and creative. this method is designed or created with the aim of making teachers, students and parents more aware and understanding how to learn to read the beginning. The main purpose of this multimedia based method, is to increase the reading interest of elementary school students who are very low and experiencing a decline. It is also expected that after students understand this method. this study aims to apply research method using quantitative research methods. sampling and data collection techniques used research instruments, namely questionnaire sheets and pretest and posttest test sheets to determine the results of early reading interest in second grade students of SDN Ketegan. To find out how much influence the use of the multimedia based glann doman method on early reading interest in students.